Os etnoconhecimentos botânicos dos Paiterey e as repercussões no território: uma prévia análise na Aldeia Paiter da Linha 09 - Terra Indígena Sete de Setembro - Tássia Karina Alexandre de Medeiros; Adnilson de Almeida Silva; Gasodá Wawaeitxapôh Suruí; Isaac Costa Araújo Filho; Nicolas Floriani (Confins)
Medicinal plants are fundamental elements for human healthing in many parts of Brazil especially for indigenous peoples who holds an ethnobotanical knowledge and use it in the treatment of their diseases. As we know, the popular use of these plants is an ancient practice with accumulation of knowledge which goes on from generation to generation. As a result of the inclusion of indigenous peoples in society, by means of comprehensive search for better living conditions or even to the improvement and/or training, this empirical knowledge so many used in the middle space gave in to the Indian laboratory medicine, somehow with the progress of scientific knowledge at the expense of extensive experience brought by indigenous people. Then this study examines specifically the case of the Paiter Village from Line 09, nominated as Indigenous Land ‘Sete de Setembro’, placed approximately 50 kilometres from Cacoal city, Rondônia State. As it was said, this research is a study of case among the Paiterey, and it follows a qualitative approach with technical designs and experimental doings. So it investigates the use of medicinal products from the forest of this region as a basis for health which is related to the indigenous practices, as well as its re-signification as an important element in the cooperation strategies among social actors such as the Academy, while these peoples look for the visibility of their culture and the recognition of their socio-territorial rights associated with the training and qualification of future indigenous leaders – even against the external pressure which implies losses of the biodiversity on their territory.